How smart schools get and keep community support - Carroll, Susan Rovezzi; Carroll, David (Bloomington, Ind National Educational Service, 1994)
Table of contents: The stage is set for a new way of thinking, doing your demographic homework, image matters (whether we like it or not)....
Includes refenrences and resources
Keywords: Tham khảo